Assessing Settlement Suitability Using Road Network Analysis for Sustainable Urban Planning in Ambon City, Indonesia - Rakuasa, Heinrich; Budnikov, Viktor Vladimirovich (Applied Engineering, Innovation, and Technology, 2024)
The availability of infrastructure, particularly the road network, is a critical factor influencing the spatial distribution and suitability of land for settlement development in Ambon City. This study aims to assess settlement suitability by analyzing the relationship between settlement areas and their proximity to the road network, with a focus on supporting sustainable urban planning. Using road network data and SPOT 6 satellite imagery, the research employs a buffer technique to categorize settlements into three zones based on their distance from the nearest road: less than 100 meters, between 100 and 750 meters, and more than 750 meters. The findings reveal that settlements located within 100 meters of the road network cover 8,538.43 hectares, or 26.21% of the total settlement area. Settlements situated between 100 to 750 meters from roads account for 11,634.20 hectares (35.72%), while those farther than 750 meters from the road network occupy 12,401.05 hectares, representing 38.07% of the total settlement area. These results underscore the critical role that proximity to roads plays in determining the suitability of land for residential development, with a noticeable concentration of settlements closer to transportation infrastructure. The outcomes of this study provide valuable insights for urban planners and policymakers in Ambon City, offering a spatial understanding of settlement distribution that can guide future infrastructure development and land use policies.